ANALYSIS OF INSTRUMENT VALIDITY ASSESSMENT ITEMS FOR STUDENT LEARNING ACHIEVEMENT - Muh Syauqi Malik; Maya Setia Priyadi (Jurnal Ilmiah Didaktika, 2021)
This article aims to determine the analysis of instrument validity assessment items. The formulation in this article is to explain the concept of validity, instruments, as well as a detailed discussion of the feasibility analysis of the valuation instruments. The notion of validity is a concept related to the extent to which the test has measured what must be measured. To analyze instruments to evaluate learning outcomes in the form of test items, it can be done in 2 ways, namely qualitative analysis of questions and quantitative analysis of questions. This instrument is a benchmark for student learning achievement. The assessment instruments used by educational institutions in the form of school exams or madrassas must meet the requirements of substance, construction, language, and have evidence of empirical validity. While the analysis of the validity of the quantitative test includes analysis of totality validity which includes content validity, construct validity, forecast validity, and comparison validity, and item validity analysis. Researchers used data analysis techniques using instrument analysis sheets, manual calculations, Microsoft Excel applications, and SPSS applications (Statistical Product and Service Solution). This article is presented systematically and is accompanied by supporting instructions and images so that readers can understand it more quickly and more easily.